Activation of T-bet, FOXP3, and EOMES in Target Organs From Piglets Infected With the Virulent PRRSV-1 Lena Strain - Ruedas-Torres, Inés; Gómez-Laguna, Jaime; Sánchez-Carvajal, José María; Larenas-Muñoz, Fernanda; Barranco, Inmaculada; Pallarés, Francisco José; Carrasco, Librado; Rodríguez-Gómez, Irene Magdalena (Frontiers in Immunology, 2021)
Transcription factors (TFs) modulate genes involved in cell-type-specific proliferative and migratory properties, metabolic features, and effector functions. Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogen agents in the porcine industry; however, TFs have been poorly studied during the course of this disease. Therefore, we aimed to evaluate the expressions of the TFs T-bet, GATA3, FOXP3, and Eomesodermin (EOMES) in target organs (the lung, tracheobronchial lymph node, and thymus) and those of different effector cytokines (IFNG, TNFA, and IL10) and the Fas ligand (FASL) during the early phase of infection with PRRSV-1 strains of different virulence. Target organs from mock-, virulent Lena-, and low virulent 3249-infected animals humanely euthanized at 1, 3, 6, 8, and 13 days post-infection (dpi) were collected to analyze the PRRSV viral load, histopathological lesions, and relative quantification through reverse transcription quantitative PCR (RT-qPCR) of the TFs and cytokines. Animals belonging to both infected groups, but mainly those infected with the virulent Lena strain, showed upregulation of the TFs T-bet, EOMES, and FOXP3, together with an increase of the cytokine IFN-γ in target organs at the end of the study (approximately 2 weeks post-infection). These results are suggestive of a stronger polarization to Th1 cells and regulatory T cells (Tregs), but also CD4+ cytotoxic T lymphocytes (CTLs), effector CD8+ T cells, and γδT cells in virulent PRRSV-1-infected animals; however, their biological functionality should be the object of further studies.